Complexidade e estabilidade em redes tróficas de ecossistemas de água doce - Guerra, Pedro Pontes Bueno (Universidade Federal de São Carlos, 2025)
This thesis investigates the relationship between complexity and stability in food webs of freshwater ecosystems, and is structured into two main chapters. The first chapter presents a review of the key concepts necessary to understand food web structure, stability, and complexity, together with an analysis of recent trends in the literature. In this chapter, we provide a general quantification of studies addressing these topics in freshwater ecosystems, followed by a more in-depth examination of research published in the last five years. The results highlighted the most frequently studied countries, themes, and ecosystems, while also elucidating current directions in the debate on stability and complexity. This review further revealed the growing use of multivariate approaches, reflecting the importance of integrative methods to better understand processes shaped by multiple factors. The second chapter presents an empirical study on the stability of food webs and its relationship with complexity in tropical and temperate stream communities, assessing differences in community dissimilarity across space and time. We tested hypotheses related to: (i) structural differences between tropical and temperate food webs; and (ii) factors that enhance stability in these systems. The study revealed clear differences between the structures of tropical and temperate webs, as well as divergent patterns of diversity in their composition. Only a weak correlation was found between complexity parameters and stability, suggesting increase in instability in tropical webs and increase in stability in temperate ones. These results underscore the need to improve predictive models of interactions and stability metrics, as well as to advance studies that link structural aspects of food webs to their resilience. Overall, this work seeks to provide an integrated perspective on food web complexity and stability by reviewing concepts, highlighting current research trends, and presenting an empirical case study. The findings reinforce the multifactorial and multivariate nature of these processes, while also emphasizing the importance of continued research to enhance species conservation, the management of ecosystem services, and the broader understanding of ecological processes.
Complexity and stability in freshwater ecosystem food webs
Keywords: Complexidade; Ecossistemas de água doce; Estabilidade; Redes tróficas; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA TEORICA; 13. Ação contra a Mudança Global do Clima